Women and leadership the state of play and strategies for change - Kellerman, Barbara (San Francisco Jossey-Bass, 2007)
Women and Leadership brings together in one comprehensive volume preeminent scholars from a range of disciplines to address the challenges involving women and leadership. These experts explore when and how women exercise power and what stands in their way. This groundbreaking volume offers readers an informed analysis of the state of women and leadership and offers the most informed and current thinking on
"A Warren Bennis book"--P. [ii].
Keywords: Leadership in women